Pengaruh Volume Usaha dan Total Aset terhadap Sisa Hasil Usaha (SHU) Koperasi di Kota Padang - Rialdi, Fauzi; Rino, Rino (Jurnal Salingka Nagari, 2024)
The research aims to examine how Padang City's surviving cooperative business performance are affected by company volume and total assets. To establish the research variables and determine if the independent factors have an influence on the bound variables. This study took a quantitative approach using descriptive and associative kinds. Panel data is the data type that is used. This study includes data from up to 20 savings and loan and sharia finance cooperatives in Padang City between 2022 and 2023. Business Volume (X1), Total Assets (X2), and Residual Business Results (Y) are the variables in this research. methods for analyzing data, namely inductive and descriptive analysis. One component of inductive analysis is the Chow Test. 2) The Hausman Test 3) Panel Regression Model Analysis, which shows the outcomes of REM selection. Regression analysis of panel data and E-views data processing 12. The study's findings indicate that (1) Padang City's cooperative SHU is significantly impacted by company volume and assets. (2) The SHU of cooperatives in Padang City is highly influenced by both company volume and total assets simultaneously.